2016
DOI: 10.1016/j.jpowsour.2016.03.040
|View full text |Cite
|
Sign up to set email alerts
|

(Metal-Organic Framework)-Polyaniline sandwich structure composites as novel hybrid electrode materials for high-performance supercapacitor

Abstract: Carbonized Zn-(Metal-Organic Framework)MOF-polyaniline composites for high performance of supercapacitor have been developed from zinc acetate, 8-Hydroxyquinoline, and aniline via a simple process. The as-synthesized product has been characterized by X-ray powder diffraction (XRD), Scanning electron microscopy(SEM), Fourier transform infrared spectra (FT-IR), Transmission electron microscope (TEM). The electrochemical properties of carbonized Zn-MOF/polyaniline electrode were investigated by current charge-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(62 citation statements)
references
References 56 publications
(60 reference statements)
1
61
0
Order By: Relevance
“…Based on Figure (a), at low‐frequency region, PVA‐GQD/PEDOT displays a short Warburg‐line compared to other nanocomposites, indicating that incorporation of GQD into the nanofiber has enhanced the ion diffusion between electrolyte to active material . In the high‐frequency region, it was observed that the ESR for the PVA‐GQD/PEDOT is smaller than PVA/PEDOT and PEDOT (Table ), which is in agreement with the small IR drop in GCD curve.…”
Section: Resultssupporting
confidence: 67%
“…Based on Figure (a), at low‐frequency region, PVA‐GQD/PEDOT displays a short Warburg‐line compared to other nanocomposites, indicating that incorporation of GQD into the nanofiber has enhanced the ion diffusion between electrolyte to active material . In the high‐frequency region, it was observed that the ESR for the PVA‐GQD/PEDOT is smaller than PVA/PEDOT and PEDOT (Table ), which is in agreement with the small IR drop in GCD curve.…”
Section: Resultssupporting
confidence: 67%
“…However, its poor conductivity hinders the applications in the electrochemical field. The recent progress has proved that the electric capacity can be improved prominently by introducing conductive materials such as carbon and conducting polymers into the MOF systems …”
Section: Introductionmentioning
confidence: 99%
“…To tackle this issue, it is required to enhance the intermolecular interactions and improve the synergistic effects among two key compositions. Recently, a great interest has been drawn to produce the metal-organic frameworks (MOFs) based electrode materials to enhance the capacitance and cyclic life because of their higher surface area, inherently present metallic source, ordered structure and heteroatom in organic ligand 19 20 21 . Although these MOF-based materials with high surface area and hierarchical porous structures could in-situ confine the Faradaic-active metal or metal oxide nanostructures, their electrical conductivity is still far from the expected range for ECs due to their low graphitization 22 23 24 25 26 27 .…”
mentioning
confidence: 99%